Hermann Broch und die Romantik - Wohlleben, Doren (Linguae & litterae, 2014)
For the first time, this study examines the modern novelist Hermann Broch’s epochal and trans-epochal concepts of romanticism and his ambiguous stance between traditional romanticism and modern open-mindedness where literature, philosophy, and politics intersect. Thus, it provides a new perspective on the ethical debate about proper political action in the context of conservatism, moral critique, and creative change